FRI0376 Gout knowledge, beliefs and treatment practices in a national sample of us primary care providers. (23rd January 2014) - Harrold, L.R.; Mazor, K.M.; Negron, A.; Ogarek, J.; Firneno, C.; Yood, R.A.
Abstract : Background: The vast majority of patients with gout are managed by primary care providers. However, little is known regarding these physicians' knowledge of current gout treatment recommendations and their treatment practices. Objectives: To examine in a national sample of primary care providers their knowledge, beliefs and self-reported treatment practices with regard to gout management. Methods: We conducted a national survey of a random sample of 2200 primary care providers (family practitioners and internists) in the United States in 2011. Providers were asked to report their approaches to acute, intercritical, and tophaceous gout based on three vignettes. Reported treatment practices were compared to published European and American gout treatment recommendations. Results: Eight hundred and thirty eight providers completed the self-administered questionnaire (response rate of 41% after excluding providers who reported not caring for gout patients or we were unable to contact due to incorrect addresses). Responders were more likely than nonresponders to be family practitioners as compared to internists (44% vs. 38%, p=0.01); otherwise they were similar in terms of age, gender, and region of the country. The majority of respondents were male (64%), white (68%), with >16 years in clinical practice (52%), and working over 40 hours a week (52%) in the private practice setting (63%). While 64% of providers reported reading ≥1 article on gout in the last year, only 12% were aware of any recommendations or guidelines on gout management. For the acute management of podagra, 16% would aspirate the joint and 49% counsel on decreasing intake of beef, pork, organ meats, and beer. When compared to the published recommendations, only 16% of providers would provide the suggested medical treatments including avoiding nonsteroidal anti-inflammatory drugs (NSAIDs) in the setting of renal disease, using colchicine at a dose of ≤1.8 mg a day and not instituting a urate-lowering drug in the setting of an acute attack (internists 21% vs. family practitioners 11%, p<0.001). For intercritical gout in the setting of renal insufficiently, only 3.4% of all providers would provide the recommended care including starting allopurinol (≤250 mg daily) or febuxostat (40 mg) with dosing acceleration to a serum urate level of ≤6.0 mg/dl and provide prophylaxis with colchicine (internists 5% vs. family practitioners 3%, p=0.12). Lastly for tophaceous gout, 17% would provide the recommended treatments including initiating a urate-lowering drug (allopurinol, febuxostat or probenecid) with dosing acceleration to a serum urate level of ≤6 mg/dl and prophylaxis with colchicine or an NSAID (internists 22% vs. 13% family practitioners, p<0.001). Conclusions: Internists were more likely than family practitioners to report treatment practices consistent with published treatment recommendations; however, the vast majority of both provider types did not report optimal care approaches suggesting further education is needed. Disclosure of Interest: L. Harrold Grant/Research support from: Takeda Pharmaceuticals, K. Mazor Grant/Research support from: Takeda Pharmaceuticals, A. Negron: None Declared, J. Ogarek Grant/Research support from: Takeda Pharmaceuticals, C. Firneno Grant/Research support from: Takeda Pharmaceuticals, R. Yood Grant/Research support from: Savient Pharmaceuticals: for clinical drug trial;also subinvestigator for a drug trial funded by Takeda Pharmaceuticals.